Papal Orders for Investigation on Matrimonial Dispensation as Historical and Anthropological Sources - Ivan Birta (University of Belgrade, 2019)
Papal Encyclicals to local bishops regarding matrimonial dispensation have not been used so far as historiographic and anthropological sources. In this paper, an attempt was made to verify their usability in that sense. Two Encyclicals from the Catholic Fond of the Birta Archives were separated and it was examined, through comparative analysis, to what extent these Encyclicals were useful for checking historical data about on which there are doubts, and to what extent they can offer new, not yet known and important information. Thereby of course, all limitations of such data and its adequate contextualization are taken into account. These are the Encyclicals in which the Pope urges local bishops to check the allegations in the request of the Naples nobles who want to marry, even though they are close relatives. Since other original documents on the studied topic are currently unavailable, and the material has not been sorted, integrated and published in the print form, the scope of the Papal Encyclicals as sources was checked by comparing it with publicly available digitized databases and internet presentations and encyclopedias.